Lotus root-like porous carbon for potassium ion battery with high stability and rate performance - Wang, Huanhuan (2022)
Potassium ion batteries as ideal alternatives to lithium-ion batteries are developing for promising portable device energy supply. However, the inferior rate and stability performance impede their practical applications. In this work, we fabricate the carbon-based potassium ion battery with good cycling stability and extraordinary rate performance, benefiting from i) the porous and robust structure, ii) good electronic properties and iv) suitable interlayer spacing for K+ intercalation via in-situ nitrogen doping. Specifically, the in-situ growth of nitrogen-doped lotus-root like carbon matrix contributes to porous and robust structures, which can keep the structural integrity even after long-term cycling test at high current density. Besides, the high conductivity with nitrogen doping contributes to fast current response and fast K+ kinetics, exhibiting high rate capability and high surface contribution. The enlarged interlayer spacing for facilitated K+ intercalation, together with a robust structure, result in high reversible capacity after cycling test.